Here and there - Marx, Brendan (School of Languages and Literatures, 2025)
An introspective look into loneliness, distance, and intimacy Here and There is a dreamlike depiction of the ghostly textures covering the surface of the world and those in it. The purpose of the novel is to examine how we interact with foreign spaces and what they do to identity through the lenses of Yui Nishikawa and Charlie who both either are or have navigated a foreign city for a number of years. Tokyo was chosen as the primary setting for the novel because of its unique relationship with identity and loneliness; its overwhelming anonymity despite it being the most populated city in the world. This contradiction opens the characters to questions of other contradictions; of self and other, foreign and familiar, belonging and not, of space. What interests me is what these spaces do to us, how we traverse them, fill them, or vacate them; the reformation of ourselves into something other and how these new identities find life back where they came from. The novel plays with the ideas of absence and presence and, through its focus on its descriptions of the inanimate, of architecture and contrasting spaces, tries to situate identity as a reflection of these spaces and the memories of them when they are abandoned. The question of the novel is really a question of what is left behind, of a hauntology of space and object and intimacies, how they carve themselves into identity and what remains when they are gone. The result is a dreamlike, unattached world of half things, half here and half there, half self and half other, half meaningful and half not. The novel looks to show how new spaces, new intimacies fracture then redefine, how absence can fill up various kinds of spaces, both within and without and what we are to do with the aftermath of the feeling of a neon-signed alley and the eyes of those we adored within the colours.